A chromosome‐scale Gastrodia elata genome and large‐scale comparative genomic analysis indicate convergent evolution by gene loss in mycoheterotrophic and parasitic plants. (26th October 2021) - Xu, Yuxing; Lei, Yunting; Su, Zhongxiang; Zhao, Man; Zhang, Jingxiong; Shen, Guojing; Wang, Lei; Li, Jing; Qi, Jinfeng; Wu, Jianqiang
Summary: Mycoheterotrophic and parasitic plants are heterotrophic and parasitize on fungi and plants, respectively, to obtain nutrients. Large‐scale comparative genomics analysis has not been conducted in mycoheterotrophic or parasitic plants or between these two groups of parasites. We assembled a chromosome‐level genome of the fully mycoheterotrophic plant Gastrodia elata (Orchidaceae) and performed comparative genomic analyses on the genomes of G . elata and four orchids (initial mycoheterotrophs), three parasitic plants ( Cuscuta australis, Striga asiatica, and Sapria himalayana ), and 36 autotrophs from various angiosperm lineages. It was found that while in the hemiparasite S. asiatica and initial mycoheterotrophic orchids, approximately 4–5% of the conserved orthogroups were lost, the fully heterotrophic G . elata and C . australis both lost approximately 10% of the conserved orthogroups, indicating that increased heterotrophy is positively associated with gene loss. Importantly, many genes that are essential for autotrophs, including those involved in photosynthesis, the circadian clock, flowering time regulation, immunity, nutrient uptake, and root and leaf development, were convergently lost in both G . elata and C . australis . The high‐quality genome of G . elata will facilitate future studies on the physiology, ecology, and evolution of mycoheterotrophic plants, and our findings highlight the critical role of gene loss in the evolution of plants with heterotrophic lifestyles. Significance Statement: Mycoheterotrophic and parasitic plants are very special as they parasitize fungi and plants, respectively, to obtain nutrients. We sequenced the genome of the fully mycoheterotrophic orchid Gastrodia elata, which is achlorophyllous and leaf‐ and rootless, and compared it with the genome of the obligate parasite Cuscuta australis . We found that G. elata and C. australis similarly but independently lost many genes important for normal autotrophic plants to adapt to heterotrophic lifestyles.